Effect of irrigation interval, sowing method and farmyard manure on growth and seed yield of faba bean (Vicia faba L.) in the desert plain soils of northern Sudan - W.Hammad, Ammar; A. Ali, Osman; A. Mohamed, Habiballa (Gezira Journal of Agricultural Science, 2022)
This study was conducted at the National Institute of Desert Studies (NIDS) Research Farm, on the desert plain soils of the New Hamdab Agricultural Scheme, New Hamdab, Northern State, Sudan, during the winter seasons of 2008/09 and 2009/10. The objectives of the study were to determine the effect of irrigation intervals, sowing methods and farmyard manure on the growth and yield of improved Selaim cultivar of faba bean in a desert environment, and to develop a suitable technical package for these arid areas. A split-split plot design was used with four replicates. The irrigation intervals of 7, 10 and 13 days were assigned to the main plots, the two sowing methods on flat and ridges were assigned to the sub plots while the farmyard manure (FYM) with two rates of 0 and 10 t/ha was assigned to the sub-sub plots. Irrigation intervals had significant effects on number of days to 80% maturity, number of pods/plant, number of seeds/pod, biological yield and seed yield. Sowing methods significantly affected plant population, number of days to 80% maturity and biological yield. On the other hand, FYM application led to significant differences in the number of seeds/pod and number of pods/plant. However, the effects of these factors on the harvest index, 100 seed weight and time to 50% flowering were not significant. The results showed that the best seed yield (3.29 and 2.13 t/ha) was obtained when the irrigation interval was seven days with sowing on flat surface and with the application of 10 t/ha of FYM. This package resulted in the tallest plants, highest number of pods per plant, highest number of seeds per pod and highest seed yield.    تمت زراعة الفول المصري صنف سليم المحسن تحت ظروف المناخ الجاف في تربة السهل الصحراوي بشمال السودان في الموسم الشتوي 2008/2009 و2009/2010 بمزرعة المعهد القومي لدراسات الصحراء بمشروع الحامداب الجديدة الزراعي ، الذي يقع علي خطي عرض ″ 11  ′55 °17 و ″ 11  ′58  °17 ش وخطي طول ″ 08 ′06 °31 و ″ 31 ′13 °31 ق. أجريت هذه الدراسة لتقويم اثر فترات الري وطرق الزراعة والسماد البلدي علي نمو وإنتاجية الفول المصري في تربة السهل الصحراوي. نظمت المعاملات إحصائيا باستخدام تصميم القطع المنشقة المنشقة بأربعة مكررات حيث وضعت فترات الري (7- 10- 13  يوم) في القطع الرئيسية و طريقة الزراعة  ( ارض مسطحة و سرابات) في القطع الثانوية  ومستويا السماد البلدي   (صفر و10 طن /للهكتار) في القطع تحت الثانوية. تم حساب المحتوي الرطوبي للتربة ومؤشرات النمو ومكونات الإنتاجية  وإنتاجية الحبوب والإنتاج الحيوي ودليل الحصاد.  أظهرت نتائج التحليل الإحصائي وجود فروق معنوية  لأثر الري علي عدد الأيام حتى 80% نضوج ولعدد القرون في النبات والإنتاج الحيوي وإنتاجية الحبوب، أما طرق الزراعة فأثرت معنويا في الكثافة النباتية وعدد الأيام  ل80% نضوج والإنتاج الحيوي ، بينما الأثر المعنوي لاستخدام  السماد البلدي كان في عدد الحبوب في القرن وعدد القرون في النبات. أوضحت النتائج أيضا عدم وجود فروق معنوية لفترة الإزهار حتى 50% ودليل الحصاد ووزن المائة حبة. أوضحت الدراسة أن الري كل سبعة أيام وزراعة المحصول على ارض مسطحة وإضافة  عشرة طن من السماد البلدي للهكتار هي الأفضل في زراعة الفول المصري في أراضى السهل الصحراوية حيث أدت إلي أفضل طول للنبات وأعلي عدد للقرون في النبات وللحبوب في القرن وبالتالي اعلي إنتاجية للحبوب بلغت 3.29 و2.13طن/ هكتار في الموسمين علي التوالي. عليه يوصى باستخدام هذه الحزمة لزراعة الفول فى اراضى السهل الصحراوى.